The threat of state-sovereignty and state-consent on international investment law, global development and mutual survival - Bobo, Nation (University of the Free State, 2019)
This thesis adopts a three-stage test anchored on models constructed using existing literature to enable analytical investigation of the effect of state-sovereignty on international investment law (IIL), global development and mutual survival. The threat of state sovereignty on IIL forms the bedrock of the study. IIL is effective when it realises its purpose.1 The primary purpose of IIL, as informed by international investment treaties (IITs), is to attract investment.2 The other purposes of IIL are to stimulate development and encourage international cooperation.3 The first stage test investigated the effect of giving away state-sovereignty on IIL purpose of attracting international investment, inform of, foreign direct investment (FDI). At this stage, a regression model was developed and used to analyse data extracted from IITs of 25 nation-states. The results showed that on average state-sovereignty given away by a restrictive IIT provision takes two years to attract FDI amounting to about US$33million. The findings confirmed that giving away of state-sovereignty improves effectiveness of IIL in realising its principal purpose. The second stage test focused on investigating the effect of restricting state-sovereignty on human development. A regression model was developed and used to analyse data obtained from 168 countries. The results from the analysis revealed that giving away of state-sovereignty by 1% improved human development by 0.13%. The findings confirmed that giving away of statesovereignty improves human development. The third stage test involved development of an explanatory model using rational choice theory. A model developed at third stage utilises findings of first and second stages to explain the influence of giving away state-sovereignty on global development and mutual survival. The findings of the study confirmed that giving away of state-sovereignty warrants effectiveness of IIL, global development and mutual survival. Such findings insinuates that reluctance to give away statesovereignty threatens IIL, global development and mutual survival.
Thesis (LL.D. (Mercantile Law))--University of the Free State, 2019
Keywords: International investment law; Investment treaties; State-sovereignty; State-consent; Right to development; International cooperation; Global development; Mutual survival; Globalisation; Foreign direct investment; Mega-free trade agreement